Pengaruh Pendekatan Pembelajaran Saintifik terhadap Kreativitas Belajar Siswa - Muhammad Amin (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2019)
Lack of creativity in student learning so that grouping students randomly in fifth grade makes students insecure in learning, especially for those who have not mastered some of the scientific approaches in participating in class learning. Therefore, the scientific learning approach is considered to be able to improve creativity in class V. This research was conducted in March 2018 with a sample of 21 fifth graders. This type of research is quantitative descriptive research. By using data collection techniques: observation, creativity tests, and documentation. The data obtained were analyzed using the percentage formula and product moment correlation formula. The results of the study say that: (1) the implementation of scientific learning in class V is sufficiently categorized, this is evident from the percentage of 76.6%. (2) The ability of learning creativity of fifth grade students can be said to be sufficient categories, it is proven that the percentage of students' creativity test reaches 72.6% and the ability to read individually reaches a percentage of 56-75%. (3) there is influence and magnitude of the influence of the scientific learning approach on the ability of learning creativity of fifth grade students in MINU Waru II, this is based on the calculation of product moment correlation obtained the value "r" counts 0, 638, and compared with the value "r" product moment for N = 21 in the 5% interval, the value "r" is 0.413 and for 1% interval is 0.526. Then the "r" value is interpreted. Because the result of "r" count is 0.638 at the point between 0.40 ─ 0.70 which means that in the medium high category. So the influence of the scientific learning approach to the learning creativity of fifth grade students at MINU Waru II, Waru Subdistrict, Sidoarjo Regency has significant significance.